Atypical Parkinsonism‐Dystonia Syndrome Caused by a Novel DJ1 Mutation. Issue 1 (April 2014) - Bras, Jose M.; Guerreiro, Rita J.; Teo, James T.H.; Darwent, Lee; Vaughan, Jenny; Molloy, Sophie; Hardy, John; Schneider, Susanne A.
Abstract We describe a sporadic case of atypical parkinsonism‐dystonia of subacute onset at the age of 16 years in a male from a consanguineous family. He showed marked orofacial dystonia, levodopa‐induced dyskinesia, and a stereotyped bilateral eye‐pressing movement disorder. We combined Sanger sequencing of candidate genes, homozygosity mapping, and whole‐exome sequencing. A homozygous mutation was identified disrupting a splice site in exon 5 of the DJ1 (PARK7) gene. Clinical details and a video are provided. DJ1 mutations are a rare cause of atypical complex parkinsonism. Exome sequencing is efficacious in identifying the causal gene variant.